Pulmonary arterial hypertension associated with congenital heart disease: real-world analysis of clinical characteristics, treatment patterns and outcomes from EXPOSURE. (3rd October 2022) - Escribano, P; Gaine, S; Klement, R; Muller, A; Lange, T J; Soderberg, S
Abstract: Background: Treatment patterns for patients with pulmonary arterial hypertension associated with congenital heart disease (PAH-CHD) are currently not well described. Purpose: To use real-world data from the EXPOSURE study to describe clinical characteristics, treatment patterns and outcomes of PAH-CHD patients in current clinical practice. Methods: EXPOSURE (EUPAS19085) is an ongoing, multicentre, prospective, observational study of PAH patients initiating a PAH-specific therapy in Europe and Canada. Clinical characteristics, treatment patterns, hospitalisation and mortality are described for PAH-CHD patients classified into four clinical subgroups. Baseline was considered to be within 30 days of PAH-specific treatment initiation. Results: Between September 2017 and November 2021, there were 1588 PAH patients with follow-up data in EXPOSURE, of whom 168 (11%) had PAH-CHD. Of these, 40% (N=67) had Eisenmenger's Syndrome (ES), 25% (N=42) had PAH with coincidental CHD, 21% (N=35) had PAH with left-to-right shunts, and 14% (N=24) had PAH after CHD corrective surgery. Baseline characteristics are summarised in the Table. Across the subgroups, the median age was 46–53 years. Compared to the other subgroups, at baseline, ES patients had a substantially longer time from diagnosis (median [Q1, Q3]: 12.6 [3.3, 31.5] years), a lower 6MWD (median [Q1, Q3]: 400 [309, 480] m) and were more likely to be in WHO FC III/IV (Table). The majority of patients across all subgroups initiated a new PAH-specific therapy as part of combination therapy at enrolment (Table). Treatment patterns over time for ES patients are shown in the Figure. The majority of ES patients received double or triple combination therapy at baseline. Overall, most ES patients remained on the same treatment regimen 6 months after baseline, with limited treatment escalation (Figure). The median observation period ranged between 15.0 and 23.0 months for all subgroups (Table). Incidence of all-cause hospitalisation during this time was generally comparable across subgroups (Table). All-cause mortality incidence rates (95% CI) were higher in patients with ES (6.3 [2.3, 13.7]) and PAH after CHD corrective surgery (8.1 [1.7, 23.8]) compared to the other two subgroups (Table). Conclusions: In EXPOSURE, 11% of patients were PAH-CHD patients, with ES being the most common PAH-CHD aetiology. The majority of PAH-CHD patients were enrolled on combination therapy. ES patients had a longer time from diagnosis compared to other subgroups and their treatment patterns followed a stepwise approach. At 6 months post-baseline, the majority of ES patients were on double or triple combination therapy. Hospitalisation was comparable between subgroups and mortality was higher in ES and PAH after CHD corrective surgery patients. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Actelion Pharmaceuticals Ltd, a Janssen Pharmaceutical Company of Johnson & Johnson